2004
DOI: 10.1038/sj.gene.6364061
|View full text |Cite
|
Sign up to set email alerts
|

Defining the contribution of the HLA region to cis DQ2-positive coeliac disease patients

Abstract: The major genetic susceptibility to coeliac disease is contributed by the human leukocyte antigen (HLA) region. The primary association is with the HLA-DQ2 molecule, encoded by the DQA1*05 and DQB1*02 alleles, which is expressed by over 90% of patients. The aim of our study was to perform an extensive scan of the entire HLA region to determine whether there is evidence for the presence of additional HLA susceptibility genes for coeliac disease in the Dutch population, acting independently of DQ2. In all, 16 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 32 publications
2
36
2
3
Order By: Relevance
“…DQ2.5 in cis or trans) confers the primary increased risk of coeliac disease. Interestingly, however, several studies 15,16 have shown that this risk is further increased 4-6! by homozygosity for the cis haplotype or a second DQB1*02 allele on the other haplotype (i.e.…”
Section: The Human Leukocyte Antigen (Hla) Complexmentioning
confidence: 94%
See 1 more Smart Citation
“…DQ2.5 in cis or trans) confers the primary increased risk of coeliac disease. Interestingly, however, several studies 15,16 have shown that this risk is further increased 4-6! by homozygosity for the cis haplotype or a second DQB1*02 allele on the other haplotype (i.e.…”
Section: The Human Leukocyte Antigen (Hla) Complexmentioning
confidence: 94%
“…Unfortunately, however, inadequate control for the strong linkage disequilibrium across the HLA is responsible for at least some of these claims. 23 Two recent studies using larger cohorts and careful methodology did not find significant evidence for additional HLA risk factors, 15,24 however, the question of HLA risk factors in addition to DQ2 remains unresolved.…”
Section: The Human Leukocyte Antigen (Hla) Complexmentioning
confidence: 98%
“…Heterodimer DQA1*0501-DQB1*0201/02 Dutch [65] DQ2 Homozygotes, DQA1*05-DQB1*02/DQA1*0201-DQB1*02 heterozygotes France [66] HLA-DQ2 (DQA1*0501/DQB1*0201) and DR53 Italy [67] HLA-DQ2 Netherlands [68] HLA-DQ2.5/2.5 homozygotes, HLA-DQ2.5/2.2 heterozygotes Norway [69] HLA-DQ2 (DQA 1*0501, DQB 1*0201) Spain [70] HLA-DRB1*04 (DR4) *These are some of the representative population studies from various continents.…”
Section: Europementioning
confidence: 99%
“…Approximately 95% of patients with CD carry the HLA-DQ2 allele and the remaining 5% carry HLA-DQ8 [4]. HLA genes are responsible for approximately 40% of the genetic risk for CD [5]. The other 60% of the genetic susceptibility to CD is shared between an unknown number of non-HLA genes, each of which is estimated to contribute only a small effect [6].…”
Section: Introductionmentioning
confidence: 99%